Assessment of Recreational Facilities in Federal Capital City, Abuja, Nigeria - Cyril Kanayo Ezeamaka; Olumide Akinwumi Oluwole (Indonesian Journal of Geography, 2016)
Abuja Master Plan provided development of adequate Green Areas and other Recreational Facilities within the Federal Capital City (FCC), as part of its sustainability principles and provided for these recreational facilities within each neighborhood (FCDA, 1979). However, there have been several recent foul cries about the negative development of recreational facilities and the abuse of the Master Plan in the FCC.  The motivation for carrying out this study arose from the observation that recreational facilities in Phase 1 of the Federal Capital City Abuja are not clearly developed as intended by the policy makers and thus, the need to identify the recreational facilities in the Phase 1 of FCC and observe their level of development as well as usage. The field survey revealed that the Central Business District and Gazupe have higher numbers of recreational facilities with 45 and 56. While Wuse II (A08) and Wuse II (A07) Districts have lesser recreational facilities with 10 and 17. The field survey further revealed that all the districts in Phase 1 have over 35% cases of land use changes from recreational facilities to other use. The survey shows that over 65% of these recreational facilities are fully developed. The study also shows that just about 11% of the recreational sporting facilities were developed in line with the Abuja Master Plan in Phase 1. The study revealed that recreational facilities in Phase 1 of the FCC, Abuja has not being developed in compliance with the Abuja Master Plan.